Letter : International Brigade - Stott, William
034-0111-001 RAILWAY CLERKS' ASSOCIATION OF GREAT BRITAIN AND IRELAND Telegraphic Address: FORESHADOW NORWEST LONDON (as two words) Telephone: TERMINUS 6267 (3 lines) General Secretary WILLIAM STOTT Representing the Clerical, Administrative, Professional, Technical and Supervisory Employer in all Departments of the Railways and Allied Undertakings, and London Transport. Reference P. Your WMC/HVT/F.C./438 Registered Office: 25 EUSTON ROAD LONDON N.W.1 8th December, 1938 Dear Sir Walter, INTERNATIONAL BRIGADE I am writing to ask whether you are yet in a position to tell me anything definite about this matter. I have recently been informed (1) that the half-yearly cash statements have been duly and properly audited; (2) that the I.B.D.W.A. Committee is willing to allow any Organisation that has supported the Brigade to scrutinise the list of the families that have been or are being helped and to check receipts for the amounts paid out; and (3) that the Committee has already sent to the T.U.C. a list of members of the Brigade who are Trade Unionists, and that a further list is being supplied. I am sorry to be so persistent, but the Executive Committee of the R.C.A. are being continually pressed. Yours sincerely William Stott. Sir Walter Citrine, K.B.E., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/34/111